Effect of Processing Temperature and Liquid Palm Sugar Concentration on the Physicochemical Characteristics of Adulterated Multifloral Honey - Ajeng Kurniawati; Fitranaya Arlian Cintaya Dewi; Faizah Faizah (Journal of Nutrition Explorations, 2026)
The high demand for honey in Indonesia has triggered counterfeiting practices combined with thermal processes, decreasing its quality. While studies on honey adulteration and heating exist, the specific combination using liquid palm sugar remains unexamined. This study aims to analyze the effect of adding liquid palm sugar (0-30% w/w) and heating temperatures (control, 50-90°C) on hydroxymethylfurfural (HMF) levels, water content, and color in multiflora honey. The research used a Randomized Block Design (RBD) with two replications. Data were analyzed statistically using ANOVA, followed by DMRT tests at the α = 5% level if significant effects occurred. The results showed that increasing liquid palm sugar concentration and heating temperature significantly (p < 0.05) reduced honey quality. The HMF content rose from 8.77±0.26 mg/kg in pure honey to 54.25±0.15 mg/kg, exceeding the maximum SNI 8664:2018 limit of 40 mg/kg. Higher heating temperatures significantly decreased water content (p<0.05), whereas liquid palm sugar addition increased the initial water content. Furthermore, honey lightness (L*) decreased with higher temperatures and sugar concentrations; the lowest lightness (L* = 44.75±0.54) and a shifted hue value (from 57.15±1.33° to 54.10±2.32°) occurred at 30% concentration and 90°C, producing darker color. In conclusion, adulteration with liquid palm sugar and thermal treatment significantly affect the quality parameters of multiflora honey.